Effects on body weight, eating behavior, and quality of life of a low‐energy diet combined with behavioral group treatment of persons with class II or III obesity: A 2‐year pilot study - Jan Karlsson; Marije Galavazi; Stefan Jansson; Johan Jendle (Wiley, 2021)
Summary Objective Obesity is associated with reduced health‐related quality of life (HRQoL). Outcomes of nonsurgical weight loss treatment on HRQoL are inconsistent and it is unclear how much weight reduction, or what type of treatment, is required for significant improvements. This study aimed to evaluate the effects of a lifestyle intervention program on weight, eating behaviors, and HRQoL, and to describe participants' experiences of treatment. Methods This 2‐year intervention trial in persons with class II or III obesity comprised a 3‐month liquid low‐energy diet (880 kcal/d) followed by a 3‐month reintroduction to regular foods, combined with behavioral group treatment. Results Fifty‐five participants (73% women) were included, mean (SD) age 43.2 (12.4) years, and mean body mass index 42.0 (6.0) kg/m2. Mean weight loss at 6, 12, and 24 months was 18.9%, 13.7%, and 7.2%, respectively. Short‐ and long‐term effects on eating behavior were favorable. Twelve of 14 HRQoL domains were improved at 6 months, compared to eight domains at 12 months. After 24 months, 2 of 14 domains, physical and psychosocial functioning, were improved. The treatment program was well accepted by the participants. Conclusions Substantial weight loss after 6 months was associated with extensive improvements in HRQoL, comprising the physical, psychosocial, and mental domains. Significant weight regain was observed between 6 and 24 months follow‐up. Modest weight loss after 24 months was associated with moderate improvement in physical functioning and large improvement in psychosocial functioning. The effect on psychosocial functioning is most likely related to both weight loss and behavioral treatment.